Long term perspective with LBBB: role of stress echocardiography. (25th November 2020) - Dedic, S; Boskovic, N; Giga, V; Tesic, M; Aleksandric, S; Jovanovic, I; Hadzi Tanovic, L; Mihajlovic Varbusova, I; Stojicic, M; Beleslin, B; Djordjevic Dikic, A
Abstract: Background: Previous studies have shown that left bundle branch block (LBBB), as a relatively common electrocardiographic (ECG) abnormality, represents the condition with often non benign and sometimes adverse outcome. Purpose: The Aim of our study was to determine the predictive value of a stress echocardiography test in patients with LBBB. Methods: Our study population included 189 patients (88 male, 46.6%, mean age 63.08±9.65) with diagnosed left bundle branch block who performed stress echocardiography (SECHO) according to Bruce protocol. Median follow-up of the patients was 56 months (IQR 48–71 months) for the occurrence of cardiovascular death and non-fatal myocardial infarction, repeat revascularization (coronary artery bypass grafting-CABG or percutaneous coronary intervention-PCI). Results: Out of 189 patients, 32 (16.9%) patients had positive, while 157 (83.1%) patients had negative SECHO test. During the follow up period 28 patients had major adverse cardiac event: 1 nonfatal myocardial infarction, 6 heart failure hospitalizations, 5 CABGs, 8 PCIs, while 8 patients had cardiac death. Using the Cox regression analysis, univariate predictors of adverse cardiac events were diabetes mellitus (HR 4.530 [95% CI 1.355–15.141], p=0.014), PCI (HR 4.288 [95% [95% CI 2.010–9.144], p<0.001) and positive SECHO test (HR 2.289 [95% CI 1.006–5207], p=0.048). In the multivariate analysis only previous PCI remained independent predictor of adverse events (HR 3.650 [95% CI 1.665–8.003], p=0.001). p=0.048). Using the Kaplan-Meier survival curve the patients with negative SECHO had better outcome compared to patients with positive SECHO (140/160; 87, 5% vs 21/29; 72.4%, p=0.035) and much longer event-free time (77.4±1.6 months vs 67.1±5.4 months, Log Rank 4.136, p=0.042) Conclusion: Patients with LBBB and negative SEHO test have good prognosis. Patients with history of CAD and diabetes mellitus and LBBB are at increased risk for future events and need periodical reassessment. Funding Acknowledgement: Type of funding source: None